Bioactivity of propolis extracts on the Myzus persicae Sulzer (Hemiptera: Aphididae) aphid in kale (Revista de Ciências Agroveterinárias, 2017)
Considering the importance of green peach aphid (Myzus persicae) a pest of various vegetables, the objective of this study was to evaluate the effect of propolis extract on the behavior and mortality of the aphid and to study chemically characterized propolis. Propolis used in this study was collected in Apis mellifera honeybee hives at UNIVASF on the Agricultural Sciences Campus. For the preparation of the extract, 30 g of ground crude propolis per 100 mL of hydrous alcoholic solution (70%) were used during a period of 10 days to yield the stock solution. The same extract was diluted to concentrations of 10, 20, 30 and 40% in distilled water, obtaining the extract ready for use in testing. Bioassays attractiveness (free and no-choice) and mortality were carried out using kale leaf discs immersed in the extract and in the control. Given the results, it was found that the alcoholic extract of propolis in low concentrations exerts pull on the green peach aphid. In over 20% concentrations, however, the same extract repels individuals of that species. The alcoholic extract of propolis is toxic to the green peach aphid, causing increasing levels of mortality as the concentration of the extract increases.
Keywords: green peach aphid; Brassica oleraceae; natural products; IPM.